The impact of job satisfaction on nurses’ work lives: A literature review - Aisha Hamad Al-Qahtani (20278134) (2020)
Many outcomes in nurses’ work lives are influenced by their job satisfaction. Background One of the tools that measures nurses’ job satisfaction is the McCloskey/Mueller Job Satisfaction tool. Several databases were accessed to identify studies published after 2002 that measured nurses’ job satisfaction using the McCloskey/Mueller Job Satisfaction tool and identified an outcome related to work lives of nurses. Aim The aim of this literature review was to explore the relationship between job satisfaction and outcomes related to nurses’ work lives. Methodology The framework developed by Cronin, Ryan, and Coughlan was used for this review. Articles included in this review met the following criteria: studies that used the MMSS (McCloskey/Mueller Nurse Job Satisfaction Scale) tool, articles that were written in English, studies that focused on nurses and outcomes related to nurses’ work lives, and articles that were published in peer-reviewed journals. The exclusion criteria included articles that were not from original research, articles that were written before 2002, gray literature, and studies that did not have ethical approval. The Johns Hopkins Nursing Evidence-Based Practice Tool was used to appraise each article’s quality. Results Eighteen articles were chosen for inclusion in this review. Nurses’ job satisfaction had several key impacts on nurses’ work lives. Five themes that reflected the outcomes of nurses’ job satisfaction were identified: commitment to the workplace, workplace environment, emotional status, career ladder, and accountability. Conclusions The findings show that workplace commitment, workplace environment, emotional status, career ladder, and accountability contribute to nurses’ job satisfaction. These factors need to be taken into account in developing interventions to increase nurses’ job satisfaction and their work output. Other Information Published in: QScience Connect License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/connect.2020.1